The Effect of Guided Discovery Methods on Students' Motivation and Learning Outcomes - Fitriani Kadir; Imam Permana; I Gede Purwana Edi Saputra; Azmar (Postgraduate, University of Mataram, 2023)
This research aimed to determine the effect of guided discovery methods on students' motivation and learning outcomes by compare the result on guided discovery method and conventional learning method at MAN 2 Model Makassar. The research method was true experiment with randomized posttest only control group design. The sample of the research were determined randomly by using group random sampling technique and obtained two classes. The first class was the experiment class which was taught by guided discovery method and the second class was control class which was taught by conventional method. Each class consisted of 42 students.Â The result obtaint that physics learning motivation and physics learning outcome of the students who were taught by guided discovery learning method is higher than conventional learning method.